Mattoso Câmara Jr. na Revista Letras: institucionalização da linguística e circulação do conhecimento - Resch, Annie Meireles (2019)
The present work has for objective to contemplate on the history of the linguistic knowledge starting from Joaquim's publications Mattoso Câmara Jr. in the magazine academic Letters of the Federal University of Paraná, bringing to the surface a constituent institutional politics of the process of institucionalização of the linguistics, through the understanding of the paper exercised by the teacher / author. The proposal of the work is developed starting from an articulation of the theoreticalmethodological perspectives of the History of the Linguistic Ideas in consonance with the Analysis of Speech of French line. In that sense, the conditions of production of the research corpus are related with the the periods of the gramatização proposed by Eduardo Guimarães in the middle of the years 1960, decade in that the Linguistics is imposed as compulsory subject for the Courses of Letters. Joaquim Mattoso Câmara Jr. it was one of the first ones to contribute with the linguistic knowledge in the beginning of the institucionalização and of the disciplinarização in the country, publishing and discussing themes that until then were not worked with the due importance. This way, we looked for with base in the analysis of five goods of the magazine academic Letters to contemplate on the themes discussed by the author to understand as the linguistic knowledge was being produced and published on that moment